PENERAPAN MULTIPLE INTELEGENSI BAGI ORANGTUA DI ERA MILENIAL - Ulfah Hernaeny; Harun Rasyid; Roida Eva Flora Siagian (Community : Jurnal Pengabdian Pada Masyarakat, 2021)
Intelligence in humans in general is different, which means that everyone has a different way of solving the problems they face. These different abilities or intelligences were introduced by an expert, namely Gardner, as Multiple Intelligences. Gardner, a developmental psychologist and professor of education from the Graduate School of Education, Harvard University, United States, has researched a lot about intelligence, so that various known intelligences were born. Multiple Intelligences, the concept of each person having more than one intelligence, having at least eight intelligences, namely linguistics, mathematical logic, intrapersonal, interpersonal, musical, naturalist, visual-spatial, and kinesthetic. The importance of introducing parents to some of the intelligences possessed by every child that parents need to know so that parents understand that every child is intelligent so there is no freeze and no stagnation. The purpose of this activity is to provide counseling on the application of multiple intelligences for parents in the millennial era, precisely at Taman Anyelir 3 Depok, Java. It is hoped that this training will be able to increase parents' understanding and knowledge of the Multiple Intelligences possessed by each child and be able to apply it in everyday life.